Improving public governance in South Asia - Khanna, Tejendra (2001)
The present paper deals with the issue of improvement of public governance in South Asia. Good governance is a major issue of global concern. The question of good governance has emerged as one of the major concerns for policy makers and administrators all over the world. The issue of improvement of public governance demands special attention in South Asia. This paper pointedly draws our attention to some of the important changes for the present administrative situation in South Asia which in the author's opinion are deterioration in the maintenance of law and order, decline in work culture and internal discipline in public organisations, low productivity in the use of financial resources, high level of corruption and dishonesty, poor accountability of public functionaries and decline in service-ethic and lack of serious political focus and intent aimed at effecting meaningful administrative reforms. - Reproduced
Keywords: Public administration